Virtual Tour Training as Micro-Learning Media for Senior High School Teachers - Mustika, Dona; Hasby, Hasby; Saputra, Hendri (Unram Journal of Community Service, 2024)
Virtual tour is one of the technological innovations that has great potential in providing an immersive learning experience for students, and is appropriate for use in the midst of the current industrial revolution. In addition to the existence of technology, the readiness and skills of educators to utilize the technology optimally are also needed. The results of the initial survey found that many teachers were familiar with virtual tour technology. Therefore, this service activity was carried out to provide training on virtual tours as micro media in learning. The participants of this service activity were teachers of SMA N 1 Idi Rayeuk. This virtual training used an android camera with the help of the Foxpoi 360 sphere camera application, and also the Lapentor platform. The result of this training is a virtual tour micro media for learning in high school. The response results of the training participants showed enthusiasm and interest in the development of virtual tours